Some Corrosion Problems in Agricultural Production and ways of their Solution - Knyazeva, L.G.; Zavrazhnov, A.I. (Journal of Applied Solution Chemistry and Modeling, 2022)
The analysis is given of some corrosion problems in the agro-industrial complex associated with various climatic conditions, specific operating environments for machinery and equipment, and some particular solutions are shown related to the use of anti-corrosive materials that are available and effective in agricultural production.